Effect of aromatic substitution of curcumin nanoformulations on their stability - Okonogi S. (2017)
© 2016 by the authors; licensee MDPI, Basel, Switzerland. Curcumin, a poorly water-soluble bioactive compound, was successfully loaded into three different aromatic contents of hydroxypropylmethacrylamide (HPMA)-based polymeric micelles in order to develop water-soluble curcumin nanoformulations (Cur-Nano). The stability study of Cur-Nano was done by keeping the formulations at 4, 30, and 40 °C for 90 days. The physical appearance, curcumin remaining, and particle size of Cur-Nano were examined by visual inspection, high-performance liquid chromatography, and dynamic light scattering, respectively. After the storage period, the Cur-Nano composed of 100% aromatic-substituted polymer exhibited the highest stability of curcumin (80% of curcumin remaining) with a similar particle size as measured on the first day (50–60 nm) in all storage conditions. Curcumin in Cur-Nano composed of 25% and 0% aromatic-substituted polymer was significantly less stable accordingly. The results suggested that aromatic substitution to HPMA-based polymeric micelles can significantly enhance the stability of the loaded curcumin, considerably due to the π-π stacking interactions between the aromatic groups of curcumin and the polymer. It is concluded that curcumin-loaded polymeric micelles with high substituted aromatic content can be promising candidates with good storage stability for further clinical evaluations.